Therapeutic Synergy of Combination of Kaempferia galanga and Zingiber officinale Extracts on Hyperuricemia-Induced Arterial Stiffness - Hasimun, Patonah; Muzaki, Yoga Adi Restu; Sodik, Jajang Japar; Sukmawati, Ika Kurnia; Kusriani, Herni (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Hyperuricemia, characterized by high uric acid levels, is associated with an elevated risk of cardiovascular diseases. Xanthine oxidoreductase (XOR), an enzyme central to uric acid generation, is implicated in oxidative stress and diminished vascular function. It has become a focal point for potential therapeutic interventions. This investigation aimed to assess the influence of combined ethanol extracts of Kaempferia galanga L. and Zingiber officinale (KGZE) on xanthine oxidase activity and arterial rigidity in hyperuricemic rat models. Furthermore, the research sought to explore these extracts' potential in managing hyperuricemia and its associated vascular disorders. Hyperuricemia was established in Wistar rats by administering potassium oxonate at 4.5 mg/kg via injection. A total of 25 rats were divided into five groups: a normal control group receiving 0.5% CMC, a positive control group with hyperuricemia, a reference group treated with allopurinol (1.8 mg/kgBW), and two experimental groups receiving KGZE at doses of 50 mg/kgBW and 100 mg/kgBW. All rats consumed 25% fructose in their drinking water for 28 days. This study measured uric acid levels and arterial stiffness, revealing that KGZE significantly reduced uric acid levels and improved arterial stiffness, indicating its potential as an XOR inhibitor.